2016
DOI: 10.1007/s40120-016-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Medication Therapy Management Service for Patients with Parkinson’s Disease: A Before-and-After Study

Abstract: BackgroundParkinson’s disease (PD) is a neurodegenerative disease characterized by motor manifestations, autonomic and neurological disorders and sensorial symptoms. Medication therapy management (MTM) consists of a service undertaken by pharmacists to optimize pharmacological therapy results. This way, the pharmacist monitors the treatment prescribed by the doctor and formulates a healthcare plan to guarantee the treatment’s effectiveness, safety and convenience, thereby improving the patient’s quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…The selected studies demonstrated variability of their objectives, concepts used to define medication adherence, and the methods (direct and indirect) used to measure medication adherence (Table 2). Of the 16 selected studies, 9 evaluated medication adherence after implementation of a medication adherence therapy, [13][14][15][16][17][18][19][20][21] and 5 evaluated the natural history of medication adherence in patients with PD. [22][23][24][25][26] The 2 remaining studies presented either the development and validation of a scale designed to measure the beliefs of patients with PD related to medication 27 or to culturally validate the Morisky Medication Adherence Scales (MMAS-8) for Italian patients with PD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected studies demonstrated variability of their objectives, concepts used to define medication adherence, and the methods (direct and indirect) used to measure medication adherence (Table 2). Of the 16 selected studies, 9 evaluated medication adherence after implementation of a medication adherence therapy, [13][14][15][16][17][18][19][20][21] and 5 evaluated the natural history of medication adherence in patients with PD. [22][23][24][25][26] The 2 remaining studies presented either the development and validation of a scale designed to measure the beliefs of patients with PD related to medication 27 or to culturally validate the Morisky Medication Adherence Scales (MMAS-8) for Italian patients with PD.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] The 2 remaining studies presented either the development and validation of a scale designed to measure the beliefs of patients with PD related to medication 27 or to culturally validate the Morisky Medication Adherence Scales (MMAS-8) for Italian patients with PD. 28 The main concepts used to define medication adherence varied among studies and were implicitly or explicitly described as the patient behavior in relation to the prescription, 16,22,23,25 the relationship between multifactorial aspects that impact in various domains of life, 15,17,18,28 the relationship between intentional and nonintentional factors, 13,14,24 how often the patient engages in 5 aspects of adherence behavior, 20 the relationship between factors including positive beliefs about medication, 27 26 and the domain measured by a scale 19 ( Table 2). The studies employed 7 measurement methods (direct and indirect) to assess medication adherence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To carry out MTM with PD patients, the pharmacist's expertise needs to transcend the technical knowledge about the PD pharmacological treatment.It has been estimated that the PD patients' adherence to the treatment is nearly 40%, compromising the benefits of the therapy. MTM aims at optimizing the pharmacological therapy results, so the pharmacist monitors the results of the treatment prescribed by the doctor and elaborates a healthcare plan to guarantee the treatment's effectiveness, safety, and convenience, and therefore improve the patients' QoL [249]. During this time, pharmacists can serve as invaluable partners in the care of people with PD by assisting with complex medication schedules, addressing side effects, assisting with different formulations of medications, obtaining approval for medications on emergency release, ensuring appropriate intake to maximize the absorption of medications, suggesting and monitoring diet and supplementation and guiding the choice of medication based on patient preference, other concurrent medications and medical conditions, and affordability [250]…”
Section: A) Alzheimer's Diseasementioning
confidence: 99%
“…QOL is increasingly recognized as an essential outcome in PD intervention studies [6]. Medications such as levodopa/carbidopa and surgical interventions such as deep brain stimulation show strong efficacy on improving motor symptoms and QOL [7,8]. In contrast, the efficacy of drug treatments for non-motor symptoms is equivocal and drugs for non-motor symptoms could actually interfere with the effectiveness of levodopa/carbidopa and/or aggravate motor symptoms, leading to poor QOL [5,9].…”
Section: Introductionmentioning
confidence: 99%